A Post-Keynesian Critique on Mainstream Financial Education - Batista Pereira, Fernando; Cavalcante, Anderson Tadeu Marques; Crocco, Marco (Brazilian Keynesian Review, 2023)
Financial education has attracted increased attention from governments, think tanks and international institutions in the past years. Nonetheless, the prevalent policies and practices in the field usually assume a very narrow analytical framework. This paper analyses financial education policy proposals from a post-Keynesian theoretical perspective. Most practices assume that financial education, by transferring knowledge and information to people, promotes financial capability, improving individual decisions. Our analysis shows, however, that a disregard for basic elements related to the functioning of the financial system, such as uncertainty and Minsky’s financial cycles, may compromise any financial decision. The conclusion is that financial education policies require the acknowledgement of the uncertain and imbalanced environment in which the financial decisions are made and cannot be restricted solely to the qualification of individuals.